Seed pre-treatment and early growth performance of piliostigma thonningii (schum.) milne-redhead under nitrogen amendment in Old Oyo national Park, Nigeria (2023)
Survival of wildlife in protected areas is dependent on innate attributes and response of vegetation to climate change. Piliostigma thonningii holds promise for wildlife conservation in Old Oyo National Park, but its population is threatened by physical dormancy. There is dearth of information on long-term benefits of its seed pretreatment and early growth response to nitrogen fertilizer. This study assessed effects of acid scarification on germination and early growth of P. thonningii under different nitrogen application rates. Seeds harvested from three purposively selected seasonal wetlands in Old Oyo National Park (OONP) were treated with 1N H2SO4 at durations ranging from 0 – 120 minutes in three replicates. Germinated seeds were enumerated over a 14-day period. Top soils from the wetlands were randomly sampled using soil auger in three replicates for physical and chemical analyses, and for early growth study with Urea fertilizer at rates 0, 50 and 100 kg/ha in experimental pots in completely randomized design. Growth and dry matter were assessed using ANOVA at P.05. Germination commenced in control treatments at 14 days after plating (DAP) and was low (13.3%). Germination progressively increased in acid treatment. At 5 DAP for soaking for 30 minutes gave 46.67%; while it was 96.67% at 40 minutes at 14 DAP. Higher soaking times gave 100% germination by 14 DAP, but with low growth vigor. The response of P. thonningii to Urea application was significantly higher in number of leaves at 12 weeks than in other rates. Other growth parameters are not significantly different at all rates. The biomass yield of P. thonningii was 1.98 g 0.21and 2.6 g 0.36 root and shoot dry weights at 6 weeks after sowing (WAS); and 7.3 g 0.04 root and 6.4 g 0.95 shoot dry weights at 12 WAS. Piliostigma thonningii can restore and improve wildlife abundance to mitigate climate change effects in the Park.